Investigation on the effect of monoglyceride concentration on palm oil based alkyd resin preparation - Ridzuan, Ramli; Ong, Huei Ruey; Hong, Chi Shein; Khan, Maksudur R.; Yunus, R. M.; Rohaya, Mohamed Halim; Astimar, Abdul Aziz; Zawawi, Ibrahim; Islam, Muhammad Remanul (Malaysian Palm Oil Board, 2021)
Alcoholysis and esterification are useful methods to prepare polyalkyds from vegetable oils. Reaction parameters and different concentration of raw materials have showed a significant role on the properties of the formulated polyalkyds. The formation of monoglyceride (MG) and diglyceride (DG) during the synthesis and their ratio may have a significant role on the properties of the polyalkyds. The goal of the present paper was to investigate the effect of MG to DG ratio on alkyd resin synthesised from palm oil by alcoholysispolyesterification reactions catalysed by homo-hetero catalytic system. Different ratios of MG:DG were obtained from alcoholysis reaction by taking samples at different reaction times. The formation of the alkyd resin was confirmed by Fourier transform infrared (FTIR) spectroscopy with the presence of ester group (C-O-C). The molecular weight of alkyd resin was determined by gel permeation chromatography (GPC). The alkyd resin prepared at higher MG:DG ratio exhibited higher initial rate of polyesterification reaction with higher molecular weight. In addition, the film of alkyd resin prepared from higher MG:DG ratio presented better pencil hardness and chemical resistivity.